SPATIAL SPILLOVERS AND MACROECONOMIC INTERDEPENDENCIES IN AFRICA: A COMPARATIVEANALYSIS OF SPATIAL PANEL ECONOMETRIC MODELS - Musa, S. A.; Adenomon, M. O.; Maijama, B.; Adehi, M. U. (FUDMA Journal of Sciences, 2025)
This study employed spatial panel econometric techniques to analyze macroeconomic interdependencies across 49 African countries from 2010 to 2023, focusing on the role of trade balance (TB), foreign direct investment (FDI), interest rates (IR), exchange rates (EXR), and consumer price index (CPI) in influencing GDP. Traditional panel models often neglect spatial spillovers, leading to biased estimates; thus, we estimate spatial lag (SAR), spatial error (SEM), and combined SARAR models using Maximum Likelihood Estimation (MLE) and Generalized Method of Moments (GMM). The results of the analysis reveal that TB is the only consistently significant economic driver of GDP (coefficients ranging from 0.0571 to 7.0794, p < 0.01), while foreign direct investment, interest rate, exchange rate, and consumer price index show no significant effects. Spatial diagnostics confirm strong cross-country dependencies, with spatial autoregressive coefficients (0.58–1.29, p < 0.01) indicating positive spillovers and spatial error coefficients (ranging from -0.999 to 0.2569) capturing unobserved shock transmissions. Hausman tests (χ² = 3.53, p = 0.74) validate random effects specifications, suggesting unobserved regional heterogeneity is best modeled as uncorrelated with regressors. The findings underscore the necessity of spatial econometric approaches in macroeconomic analysis, particularly for policy formulations targeting trade-driven growth and regional economic integration in Africa. Policymakers should prioritize trade-enhancing strategies while accounting for spatial spillovers to maximize cross-border economic synergies.